The Influence of Lifestyle, Prestige, Promotion and Price toward Consumptive - Putra, Aditya Dwi (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
One of the businesses that is currently developing is a coffee shop or what is often referred to as a coffee shop. The trend in the Coffee Shop business is that drinking coffee is not an ordinary activity. The Coffee Shop is now not just a place to enjoy coffee, but the coffee shop has turned into a multifunctional one, namely as a place to do assignments, meet with co-workers, take selfies, and live music. This study aims to look at the influence of lifestyle, prestige, promotion, and price on consumers at the Coffee Shop On Mada Rantauprapat. The researchers used quantitative research methods, The results of this study indicate that the partial regression test T-test. Lifestyle variables do not significantly affect consumption, The Prestige variable has a positive and significant effect on consumption, The promotion variable has no significant effect on consumption, and The price variable has no significant effect on consumption, from the results conclusion the variables of Lifestyle, Prestige, Promotion and Price together have a positive and significant effect on the consumptive variable.